A Review of Biofilm Formation of Staphylococcus aureus and Its Regulation Mechanism - Qi Peng; Xiaohua Tang; Wanyang Dong; Ning Sun; Wenchang Yuan (MDPI AG, 2022)
Bacteria can form biofilms in natural and clinical environments on both biotic and abiotic surfaces. The bacterial aggregates embedded in biofilms are formed by their own produced extracellular matrix. Staphylococcus aureus (S. aureus) is one of the most common pathogens of biofilm infections. The formation of biofilm can protect bacteria from being attacked by the host immune system and antibiotics and thus bacteria can be persistent against external challenges. Therefore, clinical treatments for biofilm infections are currently encountering difficulty. To address this critical challenge, a new and effective treatment method needs to be developed. A comprehensive understanding of bacterial biofilm formation and regulation mechanisms may provide meaningful insights against antibiotic resistance due to bacterial biofilms. In this review, we discuss an overview of S. aureus biofilms including the formation process, structural and functional properties of biofilm matrix, and the mechanism regulating biofilm formation.